Mergers and acquisitions in Turkey: announcement effects stock prices in ise - Avcı, Cengiz (My University, 2006)
Bu çalışma ile Türkiye’de yeralan birleşme ve devralma duyurularının hisse senetleri fiyatları üzerindeki etkileri ekonometrik testler uygulanarak araştırılmak amaçlanmıştır. Birleşme ve devralmaların çeşitleri, tarihçesi ile birleşme ve devralma dalgalarının oluşmasını açıklayan teoriler ile birleşme ve devralmaları tetikleyen motivasyonların neler olduğu incelenmiştir. Birleşme ve devralma dalgalarının oluşumu tarihsel bir perspektif dikkate alınarak açıklanmıştır. Birleşme ve devralmaların motivasyonları değerlendirildikten sonra duyuru etkisi tartışılmıştır. Bunun yanısıra Türkeye’deki durum incelenmiş ve Türkiye’de gerçekleşen birleşme ve devralmaların nedenleri ortaya konulmaya çalışılmıştır. Literatür araştırması ortaya konulduktan sonra bulgular ve sonuç ile tamamlandırılmıştır.

The purpose of this study is to analysis the announcement effect of Mergers and Acquisitions in Istanbul Stock Exchange by improving econometric test. The theoretical approach to Mergers and Acquisitions including types, history and theories explaining the rationality behind the Merger & Acquisition wave, motives of M&A is disputed. Historical perspective is taken up while discussing why merger waves occur. After completing the motivational reason with their theories the literature review about announcement effects are clarified. Furthermore, it is focused on Turkey implementation and in addition to this history and the motivations of merging firms in Turkey are deals with. Literature review is expended and detailed about announcement effect on Merger & Acquisitions. It is ended with the main findings and conclusion.
Keywords: Hisse Senetleri_Türkiye; Şirket Birleşmeleri